Effect of maillard reaction on the properties and extractable protein content of cast natural rubber latex films - Jaswan Singh, Manroshan Singh (2007)
Natural rubber latex is basically used in many applications as it has excellent properties but due to the protein allergy problem, the natural rubber glove industry is currently in dilemma. Numerous methods have been used to reduce the amount of extractable proteins in natural rubber latex Even though effective, these methods are not popular due to the additional cost of production of these latices. In this study, a different approach is used to tackle the latex protein problems This is done by crosslinking the proteins in natural rubber latex with reducing sugars. Two different types of latex (high ammonia and ammonia reduced latices) were used